Abattoir Survey of Genital Abnormalities in Jaffrabadi Buffaloes - Vala, KB; Solanki, GB; Fetar, DT; Borakhatariya, DN; Raval, RJ (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was conducted to address the prevalence and type of pathological conditions in genitalia of 100 culled Jaffrabadi buffaloes (Bubalus bubalis). Out of 100 reproductive tracts examined, 24 were normal and 76 had gross abnormalities. Among the 184 affections observed, either single or multiple, the cervical affections were found to be the maximum 84 (45.65%) followed by uterus 50 (27.17%), ovary and bursa 29 (15.76%), fallopian tube 16 (8.70%) and vagina 5 (2.71%). Out of 50 uterii examined for the histological lesions, endometritis was observed to the extent of 72 % (36 genitalia). Based on histopathological findings, uterine lesions were classified as an acute (13.89%, n = 5), subacute (19.45%, n = 7) and chronic (66.67%, n = 24) endometritis. Among the oviducts, 16 (8.70%) tubal affections were noticed to be of salpingitis. Of these, mild (+), moderate (++) and severe (+++) degree of salpingitis was found in 3 (18.75%), 4 (25.00%) and 9 (56.25%) fallopian tubes, respectively. Biometrically, right side ovary, fallopian tube as well as uterine horn were found to be larger than the respective left organs. The study concluded that about half of the culled Jaffrabadi buffaloes have acquired cervical affections, therefore it is recommended that care should be taken while doing AI or clinical handling of the female genitalia, which can adversely affect the fertility status of animals.